2012
DOI: 10.1542/peds.2012-0900m
|View full text |Cite
|
Sign up to set email alerts
|

Iron Status in Children With Autism Spectrum Disorder

Abstract: BACKGROUND AND OBJECTIVES Children with autism spectrum disorders (ASDs) often have food selectivity and restricted diets, putting them at risk for nutritional deficiencies. Previous studies have demonstrated a high prevalence of iron deficiency (ID) in children with ASDs living in Wales, Canada, and Turkey. The objectives of this study were to determine the prevalence of ID and the adequacy of iron intake in children with ASD in the United States. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
3
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 39 publications
1
32
3
5
Order By: Relevance
“…However, this finding was not confirmed in a recent study of children with ASD in the United States (14). Of interest, a small subset of children with ASD and ID/IDA also appeared to be non-responsive to oral iron therapy (15), i.e.…”
contrasting
confidence: 60%
“…However, this finding was not confirmed in a recent study of children with ASD in the United States (14). Of interest, a small subset of children with ASD and ID/IDA also appeared to be non-responsive to oral iron therapy (15), i.e.…”
contrasting
confidence: 60%
“…Since then, another study found that 24% of autistic patients were iron deficient (Herguner et al, 2012). However, a more recent study contradicted these findings (Reynolds et al, 2012). It is of value to note that dysregulated iron metabolism has been associated not only with ASDs, but also with ADHD (Ayhan Bilgic, 2010; Dosman et al, 2006; Herguner et al, 2012).…”
Section: : Introductionmentioning
confidence: 94%
“…A study carried out with American children found that 2% of the children (aged 2-12, n=368) had intakes less than the EAR value and the inadequacy of iron increased with age [60]. Another study reported a high prevalence of insufficient dietary iron intake in children with ASD (aged 2-12, n=33) and attributed this to their narrow food preferences [61].…”
Section: Discussionmentioning
confidence: 99%